PERTUMBUHAN DAN HASIL JAGUNG TAHAN CEKAMAN KEMASAMAN DI LAHAN GAMBUT - Durani, Hidayat; Denah Suswati (Jurnal Pertanian Agros, 2025)
This research was conducted on C-type overflow peatland in Rasau Jaya Dua Village over a period of approximately eight months, from the preparation phase to data analysis. The objective of this study was to evaluate the growth and yield performance of several acid-tolerant maize genotypes and to identify those with potential to be released as new superior varieties. The experiment was arranged in a Randomized Block Design (RBD) with five treatments and five replications. The treatments consisted of five maize genotypes developed through breeding programs: A = F15-1-Bm-2-2; B = F15-1-Cm-2-2; C = F15-1-Dm-2-2; D = F15-1-Em-2-2; and E = F15-1-Fm-2-2. Observed variables included key agronomic traits such as plant height, ear height, days to tasseling and silking, number of rows per ear, ear circumference, ear diameter, number of kernels per row and per ear, ear weight with husks, grain weight per ear, 1000-kernel weight at 14% moisture content, and grain yield per plot. Data were analyzed using analysis of variance (ANOVA). The results showed that genotype D (F15-1-Em-2-2) exhibited the greatest plant height, with an average of 215.94 cm, while genotype C (F15-1-Dm-2-2) had the shortest, at 188.24 cm. The highest yield was achieved by genotype E (F15-1-Fm-2-2), reaching 5.15 tons/ha, whereas genotype C recorded the lowest yield at 3.49 tons/ha. Several genotypes demonstrated promising performance and potential for further development as superior varieties for cultivation on acidic peatland.